2005
DOI: 10.1253/circj.69.211
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Angiotensin-Converting Enzyme I/D Gene Polymorphism on the Right Ventricular Myocardial Performance Index in Patients With a First Acute Anterior Myocardial Infarction

Abstract: eterminants of long-term left ventricular (LV) systolic function after myocardial infarction (MI) are related to several factors, including infarct size and location, 1 extension of coronary artery disease (CAD), patency of the infarct-related artery, 2 and the presence of collateral anastomoses to the infarct area. 3 Inhibition of angiotensin-converting enzyme (ACE) also improves postinfarct LV function and survival. 4 The plasma concentration of ACE is mainly genetically determined. The insertion/deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
4
13
0
Order By: Relevance
“…In addition, the Tei index closely correlates with patient prognosis, 2-5,13 hemodynamics, [14][15][16] and others. [17][18][19][20][21][22] The present study confirmed these previous findings and further demonstrated the usefulness of the Tei index in the UM-X7.1 hamster model of CHF.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the Tei index closely correlates with patient prognosis, 2-5,13 hemodynamics, [14][15][16] and others. [17][18][19][20][21][22] The present study confirmed these previous findings and further demonstrated the usefulness of the Tei index in the UM-X7.1 hamster model of CHF.…”
Section: Discussionsupporting
confidence: 88%
“…The results given in the present paper correspond to the clinical study by Moller et al, which demonstrated that an abnormal RV Tei index was present in 80% of patients with MI (13). Ozturk et al also found a significant increase in this index after anterior ST-elevation MI (14). In that study, the alteration of RV Tei index was more pronounced in patients with anterior MI.…”
Section: Discussionmentioning
confidence: 52%
“…16 In a previous study, we reported higher LVMPI and RVMPI in patients with the DD genotype than in patients with the ID genotype of the ACE gene after anterior AMI. 17 Although there have been several association studies of the polymorphism of AT1R (A/C1166) in clinical endpoints, such as MI, 18 hypertension, 11 aortic stiffness, 19 and LV mass, 20 AMI has not been studied before.…”
mentioning
confidence: 99%